SERINC2 increases the risk of bipolar disorder in the Chinese population. Issue 9 (19th July 2021) - Yang, Dong; Chen, Jianshan; Cheng, Xiongchao; Cao, Bo; Chang, Hao; Li, Xuan; Yang, Chanjuan; Wu, Qiuxia; Sun, Jiaqi; Manry, Diane; Pan, Yukun; Dong, Yongli; et al.
Abstract: Background: Although common variants in a large collection of patients are associated with increased risk for bipolar disorder (BD), studies have only been able to predict 25%‐45% of risks, suggesting that lots of variants that contribute to the risk for BD haven't been identified. Our study aims to identify novel BD risk genes. Methods: We performed whole‐exome sequencing of 27 individuals from 6 BD multi‐affected Chinese families to identify candidate variants. Targeted sequencing of one of the novel risk genes, SERINC2, in additional sporadic 717 BD patients and 312 healthy controls (HC) validated the association. Magnetic resonance imaging (MRI) were performed to evaluate the effect of the variant to brain structures from 213 subjects (4 BD subjects from a multi‐affected family, 130 sporadic BD subjects and 79 HC control). Results: BD pedigrees had an increased burden of uncommon variants in extracellular matrix (ECM) and calcium ion binding. By large‐scale sequencing we identified a novel recessive BD risk gene, SERINC2, which plays a role in synthesis of sphingolipid and phosphatidylserine (PS). MRI image results show the homozygous nonsense variant in SERINC2 affects the volume of white matter in cerebellum. Conclusions: Our study identified SERINC2 as a risk gene of BD in the Chinese population.